2024
DOI: 10.1021/jacs.4c01725
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Reduction Kinetics in the Phase-Controlled Growth on Preformed Nanocrystal Seeds: A Case Study of Ru

Quynh N. Nguyen,
Eun Mi Kim,
Yong Ding
et al.

Abstract: This study demonstrates the crucial role of reduction kinetics in phase-controlled synthesis of noble-metal nanocrystals using Ru nanocrystals as a case study. We found that the reduction kinetics played a more important role than the templating effect from the preformed seed in dictating the crystal structure of the deposited overlayers despite their intertwined effects on successful epitaxial growth. By employing two different polyols, a series of Ru nanocrystals with tunable sizes of 3−7 nm and distinct pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A study of the OER activity of Ru metal nanocrystals with different crystal structures found that fcc-Ru nanocrystals exhibited higher catalytic activity than hcp-Ru . Therefore, regulating crystal structure while regulating morphology can further enhance the performance of the catalyst. , Although fcc-Ru has excellent OER performance, its underlying mechanism has not yet been elucidated. One possibility is that the fcc phase of Ru nanocrystals is conducive to the adsorption and desorption of intermediates.…”
Section: Strategies To Enhance the Acidic Oer Activity And Stability ...mentioning
confidence: 99%
“…A study of the OER activity of Ru metal nanocrystals with different crystal structures found that fcc-Ru nanocrystals exhibited higher catalytic activity than hcp-Ru . Therefore, regulating crystal structure while regulating morphology can further enhance the performance of the catalyst. , Although fcc-Ru has excellent OER performance, its underlying mechanism has not yet been elucidated. One possibility is that the fcc phase of Ru nanocrystals is conducive to the adsorption and desorption of intermediates.…”
Section: Strategies To Enhance the Acidic Oer Activity And Stability ...mentioning
confidence: 99%